Tourists' Recommendations: WOM Becomes Digital - Aleksandar Grubor; Ksenija Leković; Slavica Tomić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Tourism is a sector in which consumers – tourists widely share their opinions, experiences and recommendations. Due to the fact that tourist services cannot be evaluated before the purchase, word-of-mouth has been recognized as an influential factor and a significant resource of information transmission in the tourism market. Word-of-mouth has an important role in tourists' decision-making processes, in which consumers – tourists rely on the suggestions from those who have experienced the service. With the increasing use of the Internet, a large number of consumers – tourists have begun to share their recommendations online. Electronic word-of-mouth refers to any positive or negative statement made by a consumer - tourist about a tourist service, which is available on the Internet. The digitalization of word-of-mouth has created numerous possibilities and challenges for hospitality and tourism marketers. This paper aims to examine the influence of traditional word-ofmouth and electronic word-of-mouth on tourists' decision-making processes. Specifically, the purpose of this study is to investigate the effects of virtual interactions among consumers – tourists as a part of tourism promotion. This paper has provided a theoretical framework of word-of-mouth (WOM) and electronic word-of-mouth (eWOM) showing that electronic word-of-mouth plays an important role in the tourists' decision-making process.
Keywords: M31; Z33; 330; tourist market; consumers; recommendations; word-of-mouth (WOM); electronic word-of-mouth (eWOM)